Model IMT-PAI: Sintesis Pustaka Sistematis Pendekatan Interdisipliner, Multidisipliner, Dan Transdisipliner Dalam Manajemen Media Dan Sumber Belajar Pendidikan Agama Islam - sulfikar muhaemin; Husnul Khatimah; Noviyanti Noviyanti; Bakri Bakri (STAI YAPIS Takalar, 2026)
Prior studies on interdisciplinary, multidisciplinary, and transdisciplinary (MIT) approaches in Islamic Religious Education (PAI) generally remain conceptual and focus on curriculum or classroom learning, leaving their specific application to the management of PAI media and learning resources systematically unexamined and without an operational model. This study addresses that gap by synthesizing the literature to formulate a model for managing PAI media and learning resources based on the three approaches. The research uses a systematic literature review with descriptive qualitative analysis of 30 primary documents selected based on thematic relevance, recency, and source credibility. The synthesis shows that: (1) the three MIT approaches can be mapped onto four integrative dimensions of PAI media management, namely philosophical-theological, pedagogical-psychological, technological-managerial, and socio-cultural; (2) synthesizing these dimensions produces a new model called the IMT-PAI Model, consisting of five cyclical components (faith-knowledge, integrative planning, collaborative development, reflective implementation, and transformative evaluation); and (3) this model differs from previous MIT models in that it specifically operationalizes disciplinary integration at the level of media and learning-resource management rather than curriculum alone. The study recommends empirical testing of the IMT-PAI Model and the formulation of PAI media development policies that remain responsive to technology while preserving Islamic values.